ORGANISASI ISLAM DAN PENGARUHNYA DALAM PEMBENTUKAN DAN PENGEMBANGAN HUKUM ISLAM DI INDONESIA - Fitriyani Fitriyani (IAIN Ambon, 2017)
The presence of Muslim reformer figures who do not “endure” to be in the prolonged establishment, doing reinterpretation against the Islamic teachings in order to meet the challenges of the period. Through their works are read by people, then inspired the birth of thought and reformation in Islam. There is also emerging in the form of formal organizations with jihad programs in order to uphold the Lord teachings in all corners of the earth and harakah-harakah tajdid (reformer movements) are continuously exploring the core of Islamic teachings. The idea to enter the Islamic law into the reality of life of Indonesian community is in line with the call to reform the Islamic law which arise in most Muslim countries since the early decades of 20th century. The reform occurs at the institutional level of religious organizations such as Muhammadiyah, Nahdlatul Ulama (NU), and the Union of Islam (Persis) which often referred to as Indonesia Islamic modern movement, aims that the Islamic law applied in Indonesia has Indonesia personality or insightful. Keywords: Islamic organization, formation, development, Islamic law in Indonesia